From virtual to reality: application of a novel 3D printing hollow model for early-stage lung cancer in the clinical teaching of thoracoscopic sublobar resection - Yang, Di; Miao, Yafei; Li, Linqian; Yu, Qing; Guo, Qiang; Li, Hefei; Zhang, Xuguang; Cheng, Shujie; Li, Jinghua; Zhang, Ke (Frontiers in Oncology, 2025)
BackgroundThe integration of medical-engineering interdisciplinary technology has transformed clinical skills and anatomical knowledge teaching. Three-dimensional printing (3DP), an innovative tool, shows promise in enhancing surgical training and anatomical understanding. This study evaluates the educational efficacy of a 3DP lung cancer model optimized for surgery in teaching thoracoscopic sublobar resection.MethodsA total of 62 clinical interns were randomly assigned into two groups: a 3D visualization (3DV) model group and a 3DP model group. Pre- and post-teaching test scores were compared to assess the effectiveness of both models in enhancing anatomical knowledge and surgical skills. Additionally, feedback was collected from the interns regarding the advantages of each model.ResultsThere was no significant difference in the pre-teaching test scores between the two groups (P > 0.05). However, post-teaching scores in the 3DP group were significantly higher than those in the 3DV group (P < 0.05). Survey feedback revealed that the 3DV group excelled in convenience (P < 0.001), while the 3DP group demonstrated superiority in the ease of knowledge acquisition and understanding of vascular spatial relationships (P < 0.001). No significant differences were found between the two groups regarding model intuitiveness and identification of the lung segment range influenced by the safety margin (P > 0.05).ConclusionThe 3DP model, featuring a transparent hollow sublobar boundary, significantly improved comprehension of complex anatomical relationships and enhanced teaching outcomes in surgical skills. It offers an innovative and effective tool for teaching thoracoscopic sublobar resection, with potential applications in surgical navigation.